Youth unemployment during economic shocks: Evidence from the metal-mining prices super cycle in Chile (2022)
We analyze the effect of an exogenous commodity shock on youth long-run unemployment, and the causal mechanisms that underlie this relationship. We use Chile as a study case and the Metal Mining Price Super Cycle between the years 2003 and 2011 as an exogenous shock. The shock in Chile has two primary phases: expansion and contraction. Expansion began in 2003 and coincides with the sustained increase in metal mining prices, reaching their maximum level in 2011. Contraction began in 2013 as prices began to fall. The Chilean labor market was significantly affected by both. We leverage the heterogeneous spatial exposure of Chilean munici-palities to the shock and use a difference-in-difference approach and simultaneous equations models with lagged variables to analyze the causal mechanisms. We find evidence that this shock negatively impacted the wage premium for education. We also provide empirical evidence of a simultaneous decrease in school enrollment rates and an increase in the labor force participation of the 15-18-year age group in mining municipalities during the shock. Finally, in the long term, this negatively impacted the employability of these individuals, increasing their likelihood of unemployment once the shock ended